DINAMIKA KARAWITAN KARATON SURAKARTA MASA PEMERINTAHAN PAKU BUWANA X DAN PAKU BUWANA XI: Suatu Komparasi Historis - Joko Daryanto (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2017)
AbstractThe reign of Paku Buwana II marked the beginning of the long journey of Karawitan Karaton Surakarta. One important phase in this journey was the era of Paku Buwana X and Paku Buwana XI. During the reign of Paku Buwana X, karawitan inside the karaton (palace) thrived and even became the focal point or center of karawitan, being recognized for its complex and refined style, its unique performance style, and its extraordinary allure in terms of its inventiveness, garap, and presentation. The height of its golden era during the time of Paku Buwana X was marked by the special attention given to various kinds of garap gending, instrumental playing patterns, and the development of wilet. After Paku Buwana X’s death, Paku Buwana XI was seemingly powerless to maintain the former glory of karawitan Karaton Surakarta throughout his reign. This was due to the declining social, political, and economic situation inside the karaton, as well as other external factors. The policies of the Dutch colonial government reduced the area over which the karaton had power, lowered its level of autonomy, restricted the king’s movement, and enforced a new political contract before Paku Buwana XI took to the throne, all of which were external factors that caused the life of karawitan in the karaton to deteriorate. Keywords: Karawitan Karaton Surakarta, Paku Buwana X, Paku Buwana XI. AbstrakMasa pemerintahan Paku Buwana II merupakan awal perjalanan panjang kehidupan Karawitan Karaton Surakarta. Salah satu fase penting dalam perjalanan tersebut adalah masa pemerintahan Paku Buwana X dan Paku Buwana XI. Ketika Paku Buwana X berkuasa karawitan karaton berkibar bahkan dijadikan kiblat sebagai pusat sumber garap karawitan yang rumit dan halus,  memiliki ciri khusus dalam penyajiannya serta memiliki daya tarik yang luar biasa dalam hal penciptaan, garap, maupun penyajian. Puncak kejayaan dan keemasan pada masa pemerintahan Paku Buwana X ditandai dengan adanya perhatian khusus terhadap berbagai garap gending, pola permainan instrumen, serta pengembangan wilet. Pasca mangkatnya Paku Buwana X, Paku Buwana XI seakan tidak berdaya mempertahankan kejayaan karawitan selama memerintah di Karaton Surakarta. Hal in dikarenakan situasi sosial politik dan perekonomian internal Karaton mengalami kemunduran, di samping faktor-faktor dari luar karaton. Kebijakan pemerintah kolonial Belanda yang mengurangi daerah bawahan (manca negara), pengurangan otonomi, pembatasan ruang gerak raja, serta adanya kontrak politik yang baru sebelum Paku Buwana XI naik tahta diduga merupakan faktor-faktor eksternal yang menyebabkan kehidupan karawitan karaton mengalami kemerosotan. Kata kunci: Karawitan Karaton Surakarta, Paku Buwana X, Paku Buwana XI